Therapeutic radiation for childhood cancer drives structural aberrations of NF2 in meningiomas - Agnihotri, Sameer; Sahm, Felix; Deimling, Andreas von (Nature Communications, 2017)
Radiation-induced meningiomas are often more aggressive than sporadic ones. In this study, the authors perform an exome, methylation and RNA-seq analysis of 31 cases of radiation-induced meningioma and show NF2 rearrangement, an observation previously unreported in the sporadic tumors.